J(Si, H) Coupling Constants in Nonclassical Transition‐Metal Silane Complexes. Issue 38 (9th August 2016) - Scherer, Wolfgang; Meixner, Petra; Batke, Kilian; Barquera‐Lozada, José E.; Ruhland, Klaus; Fischer, Andreas; Eickerling, Georg; Eichele, Klaus
Abstract: We will outline that the sign and magnitude of J (Si, H) coupling constants provide a highly sensitive tool to measure the extent of Si−H bond activation in nonclassical silane complexes. Up to now, this structure–property relationship was obscured by erroneous J (Si, H) sign determinations in the literature. These new findings also help to identify the salient control parameters of the Si−H bond activation process in nonclassical silane complexes. Abstract : The sign and magnitude of J (Si, H) coupling constants provide a highly sensitive tool to measure the extent of Si−H bond activation in nonclassical silane complexes. Up to now, this structure–property relationship was obscured by erroneous determinations of the sign of J (Si, H) in the literature. These new findings help to identify the salient control parameters of the Si−H bond activation process in nonclassical transition‐metal silane complexes.